Identités des Grecs pontiques et caucasiens : le rapport aux lieux et aux territoires - Michel Bruneau (Cahiers Balkaniques)
Abstract: the Pontic Greeks and Caucasians came from a very mountainous region on the shores of the Black Sea, characterized by a fragmentation into parallel north-south valleys. The strong geographical specificity of their territory of origin weighed on the choices of their new settlements in the Georgian or Armenian Caucasus, or in northern Greece following the Exchange of Populations of 1923. After settling in the Caucasus following the Russo-Ottoman wars in the 19th century, the Pontic Greeks had to leave these territories, in particular the governorate of Kars at the end of the First World War, for Greece where, after a quarantine in Kalamaria (Thessaloniki), they chose a site and founded their new village or urban district. Refugees from a single village or from several in Pontus or the Caucasus have thus built a new place in Macedonia or Thrace with a church, school, toponym and often commemorative monument referring to the story of their uprooting. They were thus able to maintain and transmit to subsequent generations their identity linked to their original “homeland”, and not to merge into a common identity of refugees shared with the other populations of Asia Minor.